Gritos, silêncios e sementes: as repercussões do processo de des-reterritorialização empreendido pela modernização agrícola sobre o ambiente, o trabalho e a saúde de mulheres camponesas na Chapada do Apodi/CE - Silva, Maria de Lourdes Vicente da (2014)
The study on the life trajectories of female peasants that live in Chapada do Apodi, CE is focused on the analysis of the repercussions of the process of deterritorialization by the modernization of agriculture on the environment, health, and the labor of peasant women. It describes aspects of work trajectories of women inserted in agribusiness companies of irrigated fruit production, familiar/peasant agriculture, and domestic labor, and go deeper into the repercussions of the social transformations and the environmental conflict in the ways of living and producing of these women. Besides, this paper discusses the meanings and perspective of field/farm work for peasant women in the dialectic between (agri)culture and (agri)business. Starting from the feminist criticism on the role of Science, and of women as subjects of knowledge, it utilizes the approach of the feminist methodologies to go deeper into the different looks and experiences of women as from life stories of 11 women and 04 communities, done through interviews and participant observation, having as a focus the category of work. It results the description of the peasant ways of life and work threatened by the modernization of agriculture where are exposed the results of the field research about land, production and peasant culture, the environmental issue, the meanings of work and work conditions, social and health changes. For that, we problematize aspects that analyze health among wealth and illness through territory transformations with the use of pesticide and its consequences to labor and production. From the experience of these women, the research points to a few basis for the analysis of a new feminism – the environmental-peasant. Mediated by the being/doing of the peasant women, in the confrontation between contradictions and their culture, it stands on the following characteristics: As an expression of the women in defense of the natural resources; of the recognition of nature as carrier of rights and of the defense of diversity and productive dynamics as common goods. It results from an everyday movement, guided by a political insertion in the community, home, kitchen, yard, farm, etc. Spaces in which knowledge, information and different forms of power instituted by the own women circulate. It stands on the struggle for food sovereignty and for the maintenance of bonds of solidarity and labor socialization. It has its culture grounded on peasant ethics and on the values of solidarity, with the experience marked by the notions of justice, right, honesty and equity. It makes a relation of the healthy being with the access to the common resources (such as land, water, food, and biodiversity) and the appreciation of the meanings of labor. It makes an articulation of several -inseparabledimensions that exist among environment, work, family relations, social living and health. They carry a systemic vision of care, understanding it in relation to the planet, to labor and to the human being in his entireness. The dimensions also carry the experience of the economy as production of life, recognizing the important and determinant role of women in the dispute for land and territory and in the affirmation of the peasant culture.